The Application of Convertible Bonds to Decrease the Cost of Capital in a Company Based on an Analysis of Given Instruments Traded on the Catalyst Market - Rybka, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
A developing company can obtain capital from two main sources: issuing shares and debt. Both methods have their advantages but also some risk factors. Issuing convertible bonds, a form of hybrid financing, is one way to address the risk. These financial instruments enable a company to decrease its cost of capital while also allowing investors to profit from a conversion premium. Analysis of convertible bonds traded on the Catalyst market shows that the hybrid instruments are the most efficient when the market price of the company is low and issuing shares might not bring about the desired results. Moreover, additional rights incorporated into convertible bonds enable the company to decrease the coupon rate and costs of issuing debt.